Preliminary investigation on the establishment of a new meibomian gland obstruction model and gene expression - Ming Sun; Huanmin Cheng; Zheng Yang; Jiangqin Tang; Shengshu Sun; Zhanglin Liu; Shaozhen Zhao; Lijie Dong; Yue Huang (Scientific Reports)
Abstract Meibomian gland dysfunction is a chronic ocular surface disease with a complex pathogenesis, whose main clinical manifestations are meibomian gland obstruction or/and lipid abnormalities. To explore the mechanism of MGD due to meibomian gland obstruction (MGO), we established a rat model of MGO by cauterizing the meibomian gland orifice. The morphology of the lid margins and meibomian gland orifices were visualized by slit lamp. The tear production of rats was measured by phenol red cotton thread, the tear film breakup time and corneal fluorescein staining scores of rats were detected under cobalt blue light of slit lamp. Changes in the histological structure of the meibomian gland (MG) were observed by HE staining, Oil Red O staining and immunofluorescence staining (collagen IV). RNA sequencing was used to detect differentially expressed genes in MGO and normal rats, which were validated by qPCR. In the MGO group after 4, 8, and 16 weeks, the meibomian gland orifices were closed, tear film break-up time decreased and corneal fluorescein staining score increased (p < 0.05). MG acini was smaller at 8-week and 16-week MGO rats in HE staining. Oil Red O staining showed less condensed staining in the 8- and 16-week MGO groups, while more condensed staining in the 4-week MGO group. Additionally, the basement membrane was destroyed in 16-week MGO group by immunofluorescence staining of collagen IV. Meanwhile, RNA sequencing and qPCR showed that lipid peroxidation (LPO), transient receptor potential vanilloid-3 (TRPV3) and genes in PPAR signaling pathway were differentially expressed in 16-week meibomian gland obstructive rats (p < 0.05). Consequently, meibomian gland obstruction model rats were established successfully with corneal damage and lower tear film stability. Meibomian gland obstruction is a causative factor of MGD, which led to abnormal histological structure in MG, differential expression of PPAR signaling pathway and TRPV3.